Space in Archaeological Research – Methods of Reading and Interpretation. An Outline of the Issue - Połtowicz-Bobak, Marta (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2011)
This paper explores the issue of spatial research at Palaeolithic sites, discussing spatial analyses and their significance both at individual sites and at a regional scale. Interpretations of immovable and movable objects, the role of refitting analyses, and at a regional scale the importance of raw materials analyses are all addressed.
Przestrzeń w badaniach archeologicznych – metody czytania i interpretacji
Keywords: space; Palaeolithic; site; regional contacts